LEGAL PROTECTION FOR PUBLIC HEALTH AGAINST THE IMPACT OF FOREST FIRES IN INDONESIA - Aliya, Choniyya Fanya (Pusat Unggulan Ipteks-PUI Universitas Jambi, 2023)
Forest fires in Indonesia have become a recurring issue, significantly affecting public health. This journal addresses the topic of legal protection for public health in Indonesia in the face of the consequences of forest fires. Beyond causing losses to ecosystems, forest fires in Indonesia pose a significant risk to public health. This paper aims to analyze the legal protection for public health against the impacts of forest fires in Indonesia. The methodology is normative legal research with a legislative and case law approach. The research results indicate that the legal protection for public health against the impacts of forest fires in Indonesia is still inadequate and needs improvement through enhanced regulations and more effective law enforcement. The study has analyzed the legal protection for public health against the impacts of forest fires in Indonesia. The findings show that existing regulations are still inadequate and need improvement to provide better protection for public health. Additionally, more effective law enforcement is required to prevent forest fires and reduce their impact on public health. Therefore, regulatory improvements and more effective law enforcement are necessary to enhance legal protection for public health against the effects of forest fires in Indonesia.